Mediasi di Luar Pengadilan Sebagai Alternatif Penyelesaian Sengketa Perkawinan - Salsabila, Almas; Auliadi, Rizki (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to deepen knowledge about out-of-court mediation as an alternative form of resolving marital disputes and how to do it. Resolving it through non-litigation settlement based on applicable law. The method applied is normative, with relevant research sources. The dispute is caused by a lack of understanding of the husband and wife regarding the values of marriage based on marriage law. Disputes that are not resolved will end in divorce can be caused by various factors such as: economy, age, and non-fulfillment of rights and obligations. to prevent divorce, the disputing parties can make efforts to resolve the dispute peacefully. The method is to appoint a mediator who is neutral from both the husband and wife. Based on this concept, a mutual agreement in resolving family problems can be resolved peacefully and accepted by both parties. The mediator in mediation is the second stage in resolving disputes, where the first stage carried out by the parties is trying to resolve it themselves and if it fails, then in this process the mediator will help. This second process includes a non-litigation settlement that takes a short time, is cost-effective, accepted by the parties and maintains the confidentiality of the disputing parties. Husband and wife should understand each other to provide accurate and undisguised information to the mediator to make it easier to resolve the problem.